Addiction and religiosity in facing suicide: A qualitative study on meaning of life and death among homeless people - Ines Testoni; Salvatore Russotto; Adriano Zamperini; Diego De Leo (Mental Illness)
This qualitative research explores the relationship between religiosity, suicide thoughts and drug abuse among 55 homeless people, interviewed with interpretative phenomenological analysis. Analyzing the thematic structure of the participants’ narrations, important main themes appeared in order to avoid suicide, among which family, the certainty of finding a solution and the will to live. However, the suicide ideation inheres in about 30% of participants, almost all believers, addicted and/or alcoholics. Results suggest that religiosity and meaning of death neither prevent from substances abuse and alcoholism, nor is a protective factor against suicide ideation. Meanings of life are the most important reasons for living, and when they are definitively considered unworkable, alcohol and drug help to endure life in the street. A specific model is discussed.